2012
DOI: 10.1177/1091142112448416
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Excise Tax Effects of the Property Tax

Abstract: The authors analyze the excise tax effects of a general property tax from the perspective of a small open economy facing a perfectly elastic supply of capital. The model differs from most that have appeared in the literature in the following ways: (1) the property tax is applied in a four-sector model with three taxed sectors-manufacturing, housing, and services, and a tax-exempt agricultural sector. Only manufacturing and agriculture produce tradable goods; (2) the analysis considers an ''intermediate run'' t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Empirical testing of more complicated general equilibrium models of tax incidence in housing markets is still in its infancy. One recent advance is that of Muthitacharoen and Zodrow (2012). Using a simulation model calibrated using U.S. input-output data, the authors found that the incidence of a higher property tax would fall mainly, but not entirely, on the residents of the taxing jurisdiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical testing of more complicated general equilibrium models of tax incidence in housing markets is still in its infancy. One recent advance is that of Muthitacharoen and Zodrow (2012). Using a simulation model calibrated using U.S. input-output data, the authors found that the incidence of a higher property tax would fall mainly, but not entirely, on the residents of the taxing jurisdiction.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent contribution to the literature included in this survey is that of Muthitacharoen and Zodrow (2012). This piece of research is notable for the realism of the analysis:…”
Section: Renters and Tax Incidence: Empirical Evidencementioning
confidence: 99%
“…Due to consumer mobility and capitalization, the benefit view contends the property tax has zero efficiency costs and no distributional consequences (Hamilton 1976). As a result, property taxation does not distort any production, consumption, or location decisions, and it leads to efficient levels of local public expenditures (Muthitacharoen and Zodrow 2010). This view has been extended and empirically tested by Fischel (1975Fischel ( , 2001, White (1975), Oates (1969), and Oates and Schwab (1988) among others.…”
Section: Property Tax Burdenmentioning
confidence: 90%
“…On the other hand, the new or capital view describes the property tax as a profits tax on capital income or as a tax on the use of capital in a local jurisdiction (Mieszkowski 1972;Zodrow and Mieszkowski 1986), which leads to many distortions, including: reductions in the intensity of production and consumption of capital-intensive goods, decreases in the supply of capital to the taxing jurisdiction, inefficient allocation of businesses and households among local jurisdictions, and underprovision of public goods and services from concerns about tax-induced out-migration of mobile capital (Muthitacharoen and Zodrow 2010;Ross and Yinger 1999;Zodrow 2001;Zodrow and Mieszkowski 1986;Wilson 1986). Although there are stark differences between these debated and competing viewpoints of property tax incidence, the two views are not completely at odds with each other and reconciliations between the two are often noted (Muthitacharoen and Zodrow 2010). In particular, models of the new or capital view have been derived with consistencies to the benefit view with respect to interjurisdictional competition, varying tastes for local public services and sorting out of the population based upon these individual tastes, land use zoning, and residents bearing the entire property tax burden of a taxing jurisdiction (Zodrow and Mieszkowski 1986).…”
Section: Property Tax Burdenmentioning
confidence: 99%
“…In a very recent paper, Muthitacharoan and Zodrow (2012) re-examine the excise tax effects of the property tax. Muthitacharoan and Zodrow develop an intermediate time frame model of a small open economy with four sectors, manufacturing, agriculture, services and housing.…”
Section: Relevant Literaturementioning
confidence: 99%